Soft Mobility and Pedestrian Networks in Urban Areas - Galderisi, Adriana; Ceudech, Andrea (TeMA - Journal of Land Use, Mobility and Environment, 2010)
By referring to the wider strategies set up, starting from the middle of the Nineties, by the European citiesto promote a sustainable urban mobility and to the more recent concept of soft mobility, which generallyincludes pedestrian and cycling mobility, this contribution focuses on pedestrian mobility in urban areas,outlining criteria and methods for planning and designing networks of urban public open spaces, such asroads and squares, devoted to an exclusive or prevailing pedestrian use. First of all, the paper analyzes themultiple roles played by roads and squares within the cities: “axes” supporting different mobility flows,including the pedestrian ones, and in the meanwhile urban places in which different activities (commercialactivities, meeting, and so on) take place. Grounding on that, the main reasons driving toward anorganization of such spaces as urban networks have been outlined. Then, some guidelines andmethodological elements, both for planning pedestrian networks and designing their elements taking intoaccount the correspondence between foreseen uses and spatial features of each element, have beenprovided. Furthermore, the links between the pedestrian networks and the main junctions of other urbanmobility networks, as well as between the first ones and the urban contexts have been stressed. Suggestedguidelines and methodological elements have been applied and tested both on historical and suburbanareas of the city of Naples; nevertheless they represent only a first step towards the setting up of a methodfor pedestrian networks planning and design in urban areas.